Characteristics of common pathogens of urogenital tract among outpatients in Shanghai, China from 2016 to 2021 - Su Wang; Su Wang; Su Wang; Li Ding; Li Ding; Li Ding; Yixin Liu; Zhaoyang Sun; Zhaoyang Sun; Zhaoyang Sun; Wenrong Jiang; Wenrong Jiang; et al. (Frontiers Media S.A., 2023)
BackgroundUreaplasma urealyticum, Chlamydia trachomatis, and Neisseria gonorrhoeae are the prevalent causes of several genital diseases worldwide; however, their characteristics in different genders have not been well documented in Shanghai. The aim of this study is to describe the prevalence of common pathogens among outpatients, considering variations by gender and age.MethodsFrom January 1, 2016, to December 31, 2021, the urogenital swabs of 16216 outpatients aged 3-95 years from two general hospitals in Shanghai were collected. All participants' swabs were investigated for U. urealyticum, C. trachomatis, and N. gonorrhoeae by isothermal RNA-based simultaneous amplification and testing. The basic information of all participants was also recorded, including age and gender. The chi-square test was used to compare the prevalence between different genders, age groups, and infection patterns.ResultsThere were 5,744 patients (35.42%) with positive samples whose ages ranged from 7 to 80 years (33.23 ± 8.63 years), and 62.14% of them were women. The most common pathogen detected was U. urealyticum (85.08%). The highest prevalence rate of all three pathogens was found in patients aged ≤ 20 years (40.53%, 95% confidence intervals [CI]: 33.80%-47.63%). The prevalent rate of U. urealyticum was higher in men (33.36%, 95% CI: 32.19%-34.55%). The overall prevalence rates of U. urealyticum, C. trachomatis, and N. gonorrhoeae were 30.14% (95% CI: 29.44%-30.85%), 6.00% (95% CI: 5.64%-6.38%), and 2.10% (95% CI: 1.89%-2.33%).ConclusionsUreaplasma urealyticum was the most prevalent pathogen in the population, and its prevalence decreased with age. Young men aged ≤ 20 years were more frequently infected. Regular screening for sexually transmitted pathogens in different genders and age groups are warranted, particularly in young men.